Design criteria for a type of asymmetric orifice in a surge tank using CFD. Issue 1 (1st January 2018) - Gabl, Roman; Righetti, Maurizio
ABSTRACT: An asymmetric orifice can be added to a surge tank of a hydro power plant to dampen the mass oscillation. This allows a reduction of the required volume and a more stable behavior of the overall hydraulic system. In this paper, the advantage of a typical asymmetric orifice is shown in comparison with a sharp-edged geometry with two different pipe diameters. The software ANSYS-CFX is used to investigate the influence of the individual geometry parameters (radius, length, angle at the forefront) on the local head loss coefficients and the ratio of the two flow directions. Furthermore, a coefficient is analyzed based on an equation from the literature for the sharp-edged structure, which can be used comparably for the asymmetric orifice. This allows us to reach preliminary assumptions of the losses at an early state of the design process. The following adaptation can be supported by the presented guidance for the optimization process, so that a suitable geometry for the specific boundary conditions can be found.